Critical success factors of new product development in technology based firms: a case study - Ismail , Kamariah; Abdul Majid, Izaidin; Leow, Y.R; Yong, C. Y.; Thawala, W.D (2012)
In today’s advanced technological era, new products are emerging rapidly and market competition is increasing. It is important for Malaysian companies to invest more in research and development (R and D) and to develop their own design capabilities and innovative products. New product development (NPD) refers to the complete process of bringing a new product or service to the market. The quest has been going on for decades to find the answer why some businesses are so much more successful at NPD as compared to the rest. That leads to the main theme of this paper which is the critical success factors (CSFs) of NPD. This case study is based on a company in Malaysia to explore the CSFs of NPD in a technology-based company. A survey utilizing the means of interview and questionnaire were conducted to discover the factors that are important to the NPD success. The company’s strengths and weaknesses that affect NPD performance were also explored. Support with the interview results from the engineers, the role of top management is the most critical factor that leads to NPD success. As a result of the research, an adapted model of CSFs of NPD for the company was developed. Finally, the study provides discussion of the implications and recommendations for both researchers and managers in the area of NPD management.